A Major Review: Current Aspects of Ocular Behçet's Disease in Japan. (2015) - Namba, Kenichi; Goto, Hiroshi; Kaburaki, Toshikatsu; Kitaichi, Nobuyoshi; Mizuki, Nobuhisa; Asukata, Yuri; Fujino, Yujiro; Meguro, Akira; Sakamoto, Shunya; Shibuya, Etsuko; Yokoi, Katsutoshi; Ohno, Shigeaki
Abstract Diagnosis and treatment of Behçet's disease (BD) have continued to undergo new changes in recent years. We organized a Compilation Committee for Guidelines on Diagnosis and Treatment of Ocular Behçet's Disease with five ophthalmology research facilities in Japan (Hokkaido University, Health Sciences University of Hokkaido, University of Tokyo, Tokyo Medical University, and Yokohama City University), and accomplished the Major review of Current aspects of Ocular Behçet's Disease in Japan. The review consist of four chapters: introduction, ocular lesions, diagnosis, and treatment. We are very pleased if the guidelines are found to be effective and useful in improving the quality of life (QOL) and quality of vision (QOV) of BD patients in the world.